Faktor-Faktor Yang Berhubungan Dengan Motivasi Mahasiswa Untuk Melanjutkan Profesi Ners - Siswanto, Fauzi -; -, Erwin -; Woferst, Rismadefis - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Motivation can be defined as a process that could show humanâs behavior to get an achievement from inside and outside themselves. The purpose of this research was to determine the related factors such as existence, relatedness, and growth with nursing studentâs motivation to continue Nursing Profession Program. This research used a cross sectional method. The samples are chosen by total sampling method with total number of respondent 67 students. The instrument in this research was a questionnaire that had been tested of validity and reliability. The results showed that majority students are 22 years old (58,2%), students that have high motivation are 71,6%, and the students that have low motivation are 28,4%. The results of this research indicate existence factor and relatedness factors that have a significant relationship with motivation to continue the Nursing Profession Program (p value < Î±), they are existence (p value = 0,043) and relatedness (p value = 0.030). Meanwhile, the growth factor (p value = 0,445) there is no correlation with the nursing students motivation to continue the Nursing Profession Program. Based on these results, researchers suggest to Nursing Education Institutions that students go into the field before practice were given a debriefing form that is not only material, but also held a program that can increase student motivation to continue Nursing Profession Program. Keywords:Â  existence, growth, motivation, relatedness, students